KEBIJAKAN MODAL KERJA, KEBIJAKAN PIUTANG DAN PEROLEHAN LABA - Habibah, Habibah (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
This study aims to analyze the application of working capital policies and accounts receivable policies as well as their influence on profitability in all pharmaceutical subsector companies listed on the IDX as many as 11 companies. The samples used were 5 pharmaceutical sub-sector companies listed on the Stock Exchange for the period of 2009 to 2016. The sample determination method used was purposive sampling method and statistical test using panel data regression test of fixed effect model, the research method used was quantitative descriptive by carrying out the activities of collecting documents from the company's financial report data. The results of the study show that working capital policies applied by companies to implement conservative policies and working capital policies have a significant effect on earnings, while the receivable policy has no effect on profitability